Analysis Effectiveness Sale Using E-Commerce in the Digital Age: A Case Study on Generation Millennials - Prayoga, Rahmat; Sani, Indra; KN, Nurwijayanti; Febrian, Wenny Desty; Suhara, Ade (International Journal of Artificial Intelligence Research, 2024)
The purpose of study This For analyze How the use of e-commerce can increase effectiveness sale to generation millennials in the digital age. With focus on two variables independent main , namely e-commerce platforms and digital marketing strategies, research This will to study How factors the influence variable dependent , namely effectiveness sales . Data collection methods used in study This is methodology survey . Author use approach study quantitative , especially cross-sectional models, based on developmental models or growth . Approach This aiming For collect comprehensive data with fast and descriptive development individual from time to time . The target population consists of from 500 students from various campus private sector in Jakarta, with group target specific is 120 students from several programs on campus this . Size sample of 120 students chosen using total sampling, where the size sample The same with size target population. From the hypothesis First until third results calculations assisted by SemPLS that There is influence significant and positive , then Success in leveraging e- commerce platforms and digital marketing strategies depends on a deep understanding of market and consumer dynamics, as well as the ability to adapt and optimize strategies according to platform characteristics and desired business goals . Considering the characteristics and preferences of the millennial generation who focus on technology, user experience, and trust, it is important for businesses and e- commerce platforms to continue to develop relevant and sustainable strategies. This will not only allow for increased sales conversions and brand awareness, but also to maintain customer loyalty in an increasingly competitive and dynamic market.